Pengaruh Nozzle dan Pengaruh Variasi Nozzle Terhadap Mini Turbine - Hanry, Michael; Darmawan, Steven; Lubis, Sobron Yamin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Utilizing hydrokinetic energy through water turbines is a promising solution for generating renewable electricity. Water turbines play a crucial role in converting the kinetic energy of water into mechanical energy that can be used to drive electrical generators. This research focuses on the optimal design of a nozzle for water turbines to enhance the performance of hydrokinetic energy. The main objective of this study is to design and analyse an efficient nozzle for water turbines. The nozzle has a critical function in directing the flow of water efficiently and increasing the flow velocity into the water turbine. In the nozzle design, various parameters such as nozzle shape, diameter, angle, and length are considered to achieve optimal performance. The results of this research demonstrate that an optimal nozzle design can significantly enhance the performance of hydrokinetic energy in water turbines. An efficient nozzle design can increase the flow velocity, thereby resulting in increased power output from the turbine. Moreover, the use of genetic algorithms in optimizing the nozzle design aids in efficiently obtaining an optimal design.